Research on the method of measuring blasting stress waves in water-filled boreholes - The, Duc Ngo; Trong, Thang Dam; Ngoc, Thuy Ngo (Edelweiss Applied Science and Technology, 2025)
Accurately measuring stress waves generated during blasting is crucial for understanding rock failure mechanics. Traditional methods rely on large water-filled pits for measurement, which are costly and impractical for small-scale experiments. This study introduces a novel approach using water pressure sensors in small-diameter (14 mm) boreholes, providing a cost-effective and scalable alternative. Numerical simulations and experimental tests were conducted to validate this method. A conversion coefficient of 0.598 was derived to translate borehole measurement results into equivalent values for water-filled pits, accounting for borehole geometry effects on wave transmission. Advanced material models, including the Holmquist-Johnson-Cook model for concrete and the Jones-Wilkins-Lee equation for TNT, were used to simulate wave propagation accurately. Experiments using coral concrete blocks and 1 g TNT charges confirmed the reliability of this approach, with a margin of error of approximately 5% between simulation and experimental results. The findings highlight a practical and precise method for measuring transmitted stress waves in rock formations. This method not only improves measurement accuracy but also significantly reduces costs associated with stress wave analysis in blasting, making it particularly suitable for small-scale geotechnical applications.